Enhancing driver visibility at night: an advanced glass-powder paint technology approach - Abejide, Samuel; Mostafa, Mohamed; Shittu, Abdulhakim Adeoye (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Driving in low visibility regions, especially at night along a transportation facility, can be particularly dangerous. Related issues include reduced illumination leading to reducing visibility and the objects fading away into obscure darkness. In such situations, albeit some drivers suffer from deficiency (including nearsightedness and cataracts), poor visibility due to road markings becoming blur could result in several problems, including damaged night vision. This study aims at addressing these issues by providing alternative measures to improve driver visibility at night using innovative glass-powder paint technology (GPPT). An introduced driveway section located at Eastern Cape Province-South Africa is selected as reference application to compare the proposed road marking paint in the current research against the conventional one. This was conducted via a developed, grouped multinomial logistics and non-parametric, quantitative analysis model in quantum flow theory. In this study, results revealed that based on a 95% confidence level assumed equivalent to 0.05 significance level, the null hypothesis was rejected, proving that driving behaviour at night on the test section is significantly improved with the introduction of the innovative GPPT. Hence, the enhanced illumination index obtained and reduction in the blur level on the road markings indicate improved glare and night illumination.